Hubungan Pengetahuan Ibu Hamil Tentang Senam Hamil Degnan Keaktifan Senam Hamil Di Puskesmas Siman Kecamatan Siman Kabupaten Ponorogo. - Sumini Sumini (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2017)
The maternal mortality rate (MMR) in Kabuaten Ponorogo in 2013 the maternalmortality rate 102 / 100,000 KH ie 10 people, and in 2014 the maternal mortality rate127 / 100,000 KH ie 12 people. Based on data from sub-district Puskesmas Siman SimanPonorogo in getting the data AKI in 2013 that there were mother died after childbirthcaused bleeding and eclampsia are 2, 1 in 2014 and 1 in 2015. And the women whoexperienced pain and pingang discomfort during pregnancy are five pregnant women in2014, four pregnant women in 2015.The purpose of this study was to determine penetahuan pregnant women aboutpregnancy exercise in pregnancy exercise activeness in Puskesmas Subdistrict SimanSiman Ponorogo. This type of research is quantitative. The population of this research isall pregnant women UK for more than 22 weeks in Puskesmas Siman District of SimanPonorogo were 23 mothers understood sempel of this study were pregnant women UK formore than 22 weeks in Puskesmas Siman district Siman Regency Ponorogo which followspregnancy exercise were 23 mothers pregnant, the study did in November 2016. Usingsampling technique total sampling. This study uses a variable Idependen ie knowledgeand Dependent liveliness. The instrument of knowledge using questionnaires and theactivity using the list of attendees. statistical test Chi Square, p <0.05. Editing using dataprocessing, coding, scoring, tabulating.From the results of research in getting nearly half of the respondents areknowledgeable both 10 respondents (43.5%), and nearly all respondents activelyfollowing pregnancy exercise 18 respondents (78.3%), based on data on the calculationresults of the calculation of statistical test Chi Square p = 0.112 by 0.05 significantly, soHo accepted or H1 ditolak.yang means there is no relationship of knowledge of pregnantwomen about pregnancy exercise in pregnancy exercise activeness in PuskesmasSubdistrict Siman Siman Ponorogo.Pregnant women expected more increases knowledge about pregnancy exercisein order to further enhance the liveliness of pregnancy exercise. In the hope of healthworkers and cadres capable of giving information to the public about pregnancy exercise.